Pengaruh Konten Visual Influencer TikTok terhadap Minat Beli Fashion Wanita Generasi Z - Viona Marcella; Sisca Aulia (Prologia, 2026)
Generation Z in Jakarta is known for being highly responsive to digital trends and demonstrating a strong purchase intention toward various products, including fashion items—especially those promoted through visually oriented social media platforms. This study examines the influence of visual content created by TikTok influencer Nazwa Adinda on the purchase intention of women’s fashion products among Generation Z in Jakarta. The objective of this research is to determine the extent to which an influencer’s visual content can capture attention and affect young consumers’ buying intentions toward fashion products. The study is grounded in the theories of User-Generated Content (UGC), purchase intention, and personal branding. The research method employs a survey distributed to 400 female respondents aged 15–29 who are active TikTok users and follow Nazwa Adinda’s account. Data were analyzed using statistical tests, including simple linear regression. The results show that influencers’ visual content on TikTok significantly enhances purchase intention for fashion products, primarily due to the influencer’s creativity and credibility. The visual strategies employed by TikTok influencers are proven effective as digital marketing tools. The implications of these findings suggest that visual content from TikTok influencers serves not merely as entertainment but as a vital instrument in shaping young consumers’ behavior, particularly in fashion purchasing decisions. Fashion industry players can optimize the quality and authenticity of creative visual content to strengthen audience engagement and boost sales.   Generasi Z di Jakarta dikenal sangat responsif terhadap tren digital serta memiliki tingkat minat beli yang tinggi terhadap berbagai produk, termasuk fashion, terutama yang dipromosikan melalui media sosial berbasis visual. Penelitian ini membahas pengaruh konten visual dari influencer TikTok Nazwa Adinda terhadap minat beli produk fashion wanita di Generasi Z Jakarta. Tujuan penelitian adalah mengetahui seberapa besar konten visual influencer bisa menarik perhatian dan memengaruhi niat beli anak muda terhadap produk fashion. Penelitian memakai teori User Generated Content (UGC), minat beli, dan konsep personal branding. Metode yang digunakan adalah survei kuesioner sebanyak 400 responden pada perempuan usia 15–29 tahun yang aktif di TikTok dan mengikuti akun Nazwa Adinda. Data dianalisis dengan uji statistik, termasuk regresi linier sederhana. Hasilnya menunjukkan konten visual dari influencer di TikTok sangat berpengaruh dalam meningkatkan minat beli produk fashion, terutama berkat kreativitas dan kredibilitas influencer. Strategi visual influencer TikTok efektif sebagai pemasaran digital. Implikasi dari temuan ini adalah bahwa konten visual dari influencer TikTok bukan hanya sekadar media hiburan, tetapi telah menjadi instrumen penting dalam memengaruhi perilaku konsumen muda, khususnya dalam konteks pembelian produk fashion. Pelaku industri fashion dapat mengoptimalkan kualitas dan kreativitas konten visual yang autentik untuk memperkuat keterlibatan audiens dan meningkatkan penjualan.